L-Borneol 7-O-[β-D-Apiofuranosyl-(1→6)]-β-D-Glucopyranoside Alleviates Myocardial Ischemia-Reperfusion Injury in Rats and Hypoxic/Reoxygenated Injured Myocardial Cells via Regulating the PI3K/AKT/mTOR Signaling Pathway - Ziyi Tong; Gaowen Li; Chengxiao Su; Liyan Zhou; Ling Zhang; Qun Chen; Qing Xia (Journal of Immunology Research)
Ischemia/reperfusion (I/R) is a primary cause of morbidity and mortality in acute myocardial infarction (AMI). L-Borneol 7-O-[β-D-apiofuranosyl-(1→6)]-β-D-glucopyranoside (LBAG), extracted from the Radix Ophiopogonis, is the main bioactive component that may be exerting cardiovascular protection in AMI. The purpose was to examine the effects of LBAG on myocardial I/R injury (MIRI) in rats and H9c2 cells treated with hypoxia/reoxygenation (H/R). MIRI was induced through the combination of ischemia with reperfusion for 30 min and 24 h, respectively. LBAG was administered 7 days before vascular ligation. Myocardial function was detected by an electrocardiograph, histological, TTC, and TUNEL staining analyses. The influences of LBAG on the content concentration of cardiac enzymes in the serum were measured by ELISA. Moreover, H9c2 cells were exposed to LBAG or combined with AKT inhibitor (perifosine) and then exposed to H/R for simulating the cardiac injury process. Afterward, cell viability, LDH, CD-KM release, apoptosis, and autophagy were evaluated by CCK-8 and ELISA assays, flow cytometry, TUNEL, and immunofluorescence staining, respectively. Additionally, the proteins of apoptosis, autophagy, and PI3K/mTOR pathway were determined by western blotting. In I/R rats, LBAG pretreatment significantly ameliorated cardiac function, as illustrated by reducing the infarct size, myocardial autophagy, and apoptosis levels. In H/R-induced H9c2 cells, LBAG pretreatment significantly decreased cell apoptosis, LC3 II/I, and Beclin 1 levels, elevated the Bcl-2 levels, attenuated LDH, and CD-KM production. Moreover, LBAG pretreatment markedly increased the PI3K/mTOR pathway activation, and the protective influences of LBAG were partly abolished with the AKT inhibitor perifosine treatment. These findings demonstrated the protective functions of LBAG on I/R by regulating apoptosis and autophagy in vitro and in vivo by activating the PI3K/mTOR pathway.